2014
DOI: 10.1159/000366341
|View full text |Cite
|
Sign up to set email alerts
|

BMP2 Increases Adipogenic Differentiation in the Presence of Dexamethasone, which is Inhibited by the Treatment of TNF-a in Human Adipose Tissue-Derived Stromal Cells

Abstract: Background/Aims: The aim of this study was to analyze the effect of BMP2 on osteogenic differentiation of human adipose tissue-derived stromal cells (hADSCs). Methods: Cultured cells were differentiated into osteogenic lineage in the presence of BMP2. Gene expressions were determined by real time PCR. Results: BMP2 increased (2/8) or inhibited (6/8) osteogenic differentiation according to hADSCs batches. Regardless of the BMP2 action on osteogenic differentiation, BMP2 induced lipid droplet formation under an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 40 publications
(42 reference statements)
3
22
0
Order By: Relevance
“…In adipose‐derived stromal cells, BMP2 supports both adipogenic and osteogenic differentiation. In one study, addition of BMP2 to human adipose–derived stromal cells inhibited osteogenic differentiation in cells from six out of eight donors but enhanced it in cells from the remaining two donors . Similar inconsistencies were also seen in other studies.…”
Section: Introductionsupporting
confidence: 62%
“…In adipose‐derived stromal cells, BMP2 supports both adipogenic and osteogenic differentiation. In one study, addition of BMP2 to human adipose–derived stromal cells inhibited osteogenic differentiation in cells from six out of eight donors but enhanced it in cells from the remaining two donors . Similar inconsistencies were also seen in other studies.…”
Section: Introductionsupporting
confidence: 62%
“…It was shown that high dose of TNF-α suppressed the osteogenic differentiation of MSC-like cells by decreased levels of alkaline phosphatase (ALP), osteocalcin (OCN), and Runx2 [16-18]. On the other hand, several studies suggest that TNF-α may have an inhibitory effect on BMP-induced osteoblast differentiation of MSCs or preosteoblastic cells [19-21]. …”
Section: Introductionmentioning
confidence: 99%
“…Tissue regeneration may be compromised during chronic inflammation (Matzelle et al, ). Previous studies have shown that TNF‐alpha simulates the inflammatory microenvironment and activates the Wnt canonical pathway (Chen et al, ; Huang et al, , ; Khan et al, ; Lee et al, ; Lu et al, ; Mountziaris et al, ; Mukai et al, ; Qin et al, ; Tan et al, ). In this study, we analysed the effect of TNF‐alpha and DKK1 on BMP9‐induced osteogenic differentiation both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%